COMPARATIVE STUDY OF THE NOVELS ZORBA THE GREEK AND SIDDHARTHA BASED ON THE PHILOSOPHY OF LIFE. - Nair, Anjana R; Sreena K (International Journal of Research -GRANTHAALAYAH, 2025)
Literature acts as a reflection of society or human existence giving philosophical understanding and meaning of life. Zorba the Greek by Nikos Kazantzakis and Herman Hesse’s Siddhartha are two novels that dig into contrasting yet complementary philosophies of life. An existentialist perspective is presented by Zorba the Greek mainly focusing on Hedonism, the rejection of intellectual disengagement and spontaneity. Siddhartha by Herman Hesse is influenced by Buddhist philosophy—follow the path of self-discovery, spiritual transcendence and inner peace. Through the textual analysis and philosophical discourse, this paper showcases that the two novels emphasize two fundamental approaches to human conditions, engagement, and dismissal from the physical world. The comparative study inspects a philosophical framework of the novels.